2000
DOI: 10.1080/019021400269880
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Image Analysis of Lung Connective Tissue in Murine Silicosis

Abstract: Pulmonary fibrosis is a disabling consequence of many lung diseases but is difficult to quantify. Lucifer yellow CH fluorescent dye (LY) appears to stain connective tissue matrix macromolecules selectively. Laser scanning confocal microscopy can quantify the intensity of fluorescence and determine the area of fluorescent material. We hypothesized that the abundance of lucifer yellow-stained matrix macromolecules in lung tissue sections could be measured by laser scanning confocal microscopy, would reflect diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Collagen in the lungs was detected with Sirius red staining (8), which has been demonstrated to be a quantitative morphometric method for collagen determination in the lungs (1,12). Paraffin sections were deparaffinized and rehydrated with xylene-alcohol series to distilled water.…”
Section: Methodsmentioning
confidence: 99%
“…Collagen in the lungs was detected with Sirius red staining (8), which has been demonstrated to be a quantitative morphometric method for collagen determination in the lungs (1,12). Paraffin sections were deparaffinized and rehydrated with xylene-alcohol series to distilled water.…”
Section: Methodsmentioning
confidence: 99%
“…Collagen fibers in the lungs were detected with Sirius Red staining [35], which has been demonstrated to be a quantitative morphometric method for collagen fiber determination in the lungs [36,37]. Quantitative morphometric methods were used to measure the average thickness of Sirius Red positive connective tissue fibers in the alveolar regions.…”
Section: Methodsmentioning
confidence: 99%
“…The fluorescent dye Lucifer yellow selectively stains connective tissue matrix macromolecules, permitting visualization as well as quantification of collagen matrix material using advanced microscopy methods in a manner that yields comparable fibrosis values to the traditional hydroxyproline assay (3,4,58). Therefore, LSC represents an attractive alternative to standard hydroxyproline assays as well as an innovative means to rapidly quantify collagen deposition and the development of fibrosis within intact lung sections while immunostaining serial sections for other proteins of interest (3,4). The combination of Lucifer yellow and LSC demonstrated that 129Sv wild-type mice showed significant collagen deposition and development of fibrosis following silica exposure in 129Sv mice compared with untreated control.…”
Section: Discussionmentioning
confidence: 99%
“…Additional sections were stained with the fluorescent dye Lucifer yellow (0.1 mg/ml; Molecular Probes, Eugene, OR) for visualization and quantification of collagen formation. Laser scanning cytometry (LSC) represents an innovative means to rapidly quantify collagen deposition and the development of fibrosis within intact lung sections (3,4). The fluorescent dye Lucifer yellow appears to selectively stain connective tissue matrix macromolecules, permitting visualization as well as quantification of collagen matrix material using advanced microscopy methods in a manner that yields comparable fibrosis values to the traditional hydroxyproline assay (4).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation